2020
DOI: 10.3390/nu12113367
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition Management in Older Adults with Diabetes: A Review on the Importance of Shifting Prevention Strategies from Metabolic Syndrome to Frailty

Abstract: The increasing prevalence of older adults with diabetes has become a major social burden. Diabetes, frailty, and cognitive dysfunction are closely related to the mechanisms of aging. Insulin resistance, arteriosclerosis, chronic inflammation, oxidative stress, and mitochondrial dysfunction may be common mechanisms shared by frailty and cognitive impairment. Hyperglycemia, hypoglycemia, obesity, vascular factors, physical inactivity, and malnutrition are important risk factors for cognitive impairment and frail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
88
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 136 publications
(121 citation statements)
references
References 194 publications
3
88
0
8
Order By: Relevance
“…In addition, in our subgroup analysis, the trend for risk of developing retinopathy at six years was positively correlated with increasing sodium intake at baseline in patients with type 2 diabetes younger than 75 years, but there was no such trend in those older than 75 years. Therefore, the impact of nutrients on health outcomes may vary with age [ 31 ]. It has been reported that the risk of death is increased in those with type 2 diabetes older than 75 years who have low protein, vegetable, and fish intakes [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in our subgroup analysis, the trend for risk of developing retinopathy at six years was positively correlated with increasing sodium intake at baseline in patients with type 2 diabetes younger than 75 years, but there was no such trend in those older than 75 years. Therefore, the impact of nutrients on health outcomes may vary with age [ 31 ]. It has been reported that the risk of death is increased in those with type 2 diabetes older than 75 years who have low protein, vegetable, and fish intakes [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Low intake of protein including branched-chain amino acids (BCAA) in older diabetic patients in conjunction with anabolic resistance may further exacerbate sarcopenia and frailty through the decreased action of BCAA on insulinotropic and muscle protein synthesis [ 38 ]. The dietary strategy of older people with DM should advance with age from strict dietary restrictions to a diet aimed at preventing frailty [ 39 ]. A diet high in protein, vegetables, fruits, and fish, which has a high DVS, should be recommended in patients who are aged over 75 years or who have frailty as well as malnutrition [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The dietary strategy of older people with DM should advance with age from strict dietary restrictions to a diet aimed at preventing frailty [ 39 ]. A diet high in protein, vegetables, fruits, and fish, which has a high DVS, should be recommended in patients who are aged over 75 years or who have frailty as well as malnutrition [ 39 ]. Findings from this study suggest that a varied diet may be useful in preventing frailty in individuals with DM.…”
Section: Discussionmentioning
confidence: 99%
“…Very recently, nutritional and behavioral models have been proposed to contrast the increased risk of frailty in the obese, diabetic, and elderly patients (>75 years old) in whom quantities and qualities of various nutrients, including proteins, have been modified compared to younger subjects. These categories of patients should undergo anthropometric measurements and muscle function tests to allow targeted early nutrition interventions (i.e., 1.5 g/kg/day of protein intake, 2–3 hourly food intake with kidney function monitoring) and promotion of physical exercise [ 92 ].…”
Section: Role Of Proteins In Nafld and Cardiovascular Diseasementioning
confidence: 99%